Helmolds von Bosau Pons Longissimus. Archŕologische Unterwasserausgrabungen bei den Brückenanlagen neben der Slawischen und Frühdeutschen Burg Olsborg im Grossen Plöner See (Norddeutschland) - Wilke, Gerard (Wydawnictwo Naukowe UAM, 2005)
The article is aimed at presentation of results of archaeological underwater excavations of remains of the early Medieval bridge on the stronghold island Oslborg. There are vestiges of the Slavic and early German stronghold on the Grosser Plòner Lake island near Plon in north Germany. This stronghold has been repeatedly mentioned by Adam of Bremen and Helmold of Bosau - the 11th and 12th century annalists. Underwater excavations, undertaken in two study zones of 75 square meters in total, resulted in discovery of the bridge remains which revealed themselves in the form of 228 posts being elements of its bearing construction placed on the lake bottom. Dendrochronological analysis of 79 posts indicates that the bridge was constructed in 975 AD and it was rebuilt many times afterwards. Trees for subsequent reconstructions were cut down in the years 994, 995, 1005, 1008, 1011, 1012, 1013, 1025 and for the last time in 1096 AD. The excavations revealed also an assemblage of Slavic and early German pottery as well as 56 artefacts including 14 spearheads and 6 axes. These military accessories can possibly be linked with the 1075, 1128 or 1139 war, mentioned by Helmold of Bosau.
Helmond’s of Bosau Pons Longissimus. Archaeological underwater excavations of the bridge constructions of the Slavic and early German olsborg stronghold on the Grosser Ploner Lake (north Germany)